2010
DOI: 10.1210/jc.2009-2716
|View full text |Cite
|
Sign up to set email alerts
|

Possible Relevance between Prohormone Convertase 2 Expression and Tumor Growth in Human Adrenocorticotropin-Producing Pituitary Adenoma

Abstract: Our study suggests that PC2 expression and Akt phosphorylation are related at the molecular level, resulting in a change in cell cycle and an increase in pituitary adenoma size. An elevation of plasma alphaMSH could conjecture the activation of the phosphatidylinositol 3/Akt cascade in PC2-positive APPAs and may become a valuable clinical marker of tumor growth in Cushing's disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
9
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 33 publications
2
9
1
Order By: Relevance
“…Although almost half of the human corticotroph adenomas in another study were positive for PC2 with immunohistochemistry (Iino et al, 2010), we were not able to identify PC2 positive cells in the canine pituitary samples, whereas the control tissue (canine testis) stained positive, suggesting a different expression pattern in canine pituitary tissue compared to human corticotroph adenomas. This altogether indicates that Pax7 and its downstream targets may play a species-dependent differential role in pituitary tumorigenesis.…”
Section: Discussioncontrasting
confidence: 82%
See 1 more Smart Citation
“…Although almost half of the human corticotroph adenomas in another study were positive for PC2 with immunohistochemistry (Iino et al, 2010), we were not able to identify PC2 positive cells in the canine pituitary samples, whereas the control tissue (canine testis) stained positive, suggesting a different expression pattern in canine pituitary tissue compared to human corticotroph adenomas. This altogether indicates that Pax7 and its downstream targets may play a species-dependent differential role in pituitary tumorigenesis.…”
Section: Discussioncontrasting
confidence: 82%
“…The prohormone POMC is processed into ACTH in both melanotroph cells and corticotroph cells, followed by further cleavage into α-melanocyte stimulating hormone (α-MSH) by PC2 in melanotroph cells (Miller et al, 2003). In human corticotroph adenomas, 47% stained positive for PC2, whereas healthy pituitaries did not (Iino et al, 2010). Drd2 is expressed in melanotroph cells and inhibits α-MSH secretion (Garcia-Tornadu et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Compared with corticotrope pituitary tumors that were histologically classified as pure adenomas, tumors identified as adenomatous hyperplasia or hyperplasia of ACTH-producing cells have higher PC2 expression and, although not statistically significant, higher neurofilament (NF) protein expression. Together, these results led to the hypothesis that CD may originate not only from corticotrope adenomas of the anterior lobe, but also from an adenoma or adenomatous hyperplasia of ACTH-producing cells of the intermediate zone because the PC2 enzyme is predominantly expressed in this region of the pituitary gland (Iino et al 2010). In addition, increases in the levels of alpha-melanocyte-stimulating hormone, which is a PC2 processing product, in the inferior petrosal sinus were higher in these patients.…”
Section: Dopamine Agonistsmentioning
confidence: 79%
“…In the pituitary gland, pro-opiomelanocortin (POMC) is cleaved by prohormone convertases (PCs) 1 and 2 (Bertagna 1994). PC1 (PCSK1) is expressed in both the anterior and intermediate pituitary lobes, whereas PC2 (PCSK2) expression is restricted to the intermediate lobe, which is believed to regress soon after birth and, therefore, is absent in adults (Bertagna 1994, Iino et al 2010). Lamberts and colleagues showed that D2 receptor agonist-responsive tumors located in the region consisted of basophilic adenomatous tissue or multiple microadenomas accompanied by hyperplastic cell nests (Lamberts et al 1980(Lamberts et al , 1982.…”
Section: Dopamine Agonistsmentioning
confidence: 99%
See 1 more Smart Citation